Unprecedented Long‐Term Thermal Stability of 1D/2A Terpolymer‐Based Polymer Solar Cells Processed with Nonhalogenated Solvent - Jung, Hyeonwoo; Yu, Gyeonghwa; Kim, Jongyoun; Bae, Hyejeong; Kim, Minkyoung; Kim, Kwangmin; Kim, BongSoo; Lee, Youngu (Solar RRL, 2021)
Donor–acceptor (D–A) copolymer‐based polymer solar cells (PSCs) processed with nonhalogenated solvents exhibit relatively low power conversion efficiencies (PCE) due to undesirable morphological properties, including high aggregation and unfavorable orientation. Moreover, they show very poor long‐term stability owing to excessive molecular aggregation and unfavorable phase separation. Thus, novel p‐type polymers are required for high‐efficiency and long‐lived PSCs that can be processed in ecofriendly nonhalogenated solvents. Herein, a novel series of 1D/2A terpolymers (PBTPBD) composed of 4,8‐bis(5‐(2‐ethylhexyl)‐4‐fluorothiophen‐2‐yl)benzo[1,2‐b:4,5‐b′]dithiophene (BDT‐F), 1,3‐bis(thiophen‐2‐yl)‐5,7‐bis(2‐ethylhexyl)benzo‐[1,2‐c:4,5‐c′]dithiophene‐4,8‐dione (BDD), and 1,3‐bis‐(4‐hexylthiophen‐2‐yl)‐5‐octyl‐4H‐thieno[3,4‐c]pyrrole‐4,6(5H)‐dione (HT‐TPD) is synthesized and characterized for high‐efficiency and long‐lived PSCs. A PBTPBD‐50:IT‐4F blended film exhibits a favorable face‐on orientation and superior hole and electron mobility. Therefore, the corresponding PBTPBD‐50:IT‐4F PSC, processed with a nonhalogenated solvent, exhibits a high PCE of 13.64%, which is 13% higher than that of the related nonhalogenated solvent‐processed PSCs. Furthermore, the PBTPBD‐50:IT‐4F PSC maintains 82% of the initial PCE even after 204 days at 85 °C, which is the highest thermal stability achieved among PSCs processed with nonhalogenated solvents. The high‐efficiency and superior long‐term thermal stability of the PBTPBD‐50:IT‐4F PSC are attributed to the excellent miscibility of PBTPBD‐50 and IT‐4F and the suppression of the morphological changes in the photoactive layer. A novel series of 1D/2A PBTPBD terpolymers is developed for high‐efficiency and long‐lived polymer solar cells (PSCs). The PBTPBD‐50:IT‐4F PSC, processed with a nonhalogenated solvent, maintains 82% of the initial power conversion efficiency even after 204 days at 85 °C, which is the highest thermal stability achieved among PSCs processed with nonhalogenated solvents.